Interleukin 1-β responses to bacterial toxins and sudden infant death syndrome - Moscovis, Sophia M.; Gordon, Ann E.; Hall, Sharron T.; Gleeson, Maree; Scott, Rodney J.; Roberts-Thomsom, June; Weir, Donald M.; Busuttil, Anthony; Blackwell, C.Caroline (FEMS immunology and medical microbiology, 2004)
We tested the hypothesis that significantly higher IL-1β responses to toxic shock syndrome toxin (TSST) noted for parents of sudden infant death syndrome (SIDS) infants might be due in part to genetic factors such as the IL-1β (C-511T) and IL-1RN (T + 2018C) single nucleotide polymorphisms (SNP). The first objective was to assess the distribution of these polymorphisms among SIDS infants, parents of SIDS infants and controls, and two ethnic groups: Aboriginal Australians who have a high incidence of SIDS; and Bangladeshis who in Britain have a low incidence of SIDS compared with Europeans. The second objective was to assess IL-1β responses to endotoxin and toxic shock syndrome toxin (TSST) from leukocytes of smokers and non-smokers in relation to these polymorphisms. There were major differences in the distributions of the IL-1β (C-511T) SNP between Europeans and Bangladeshis ( p=0.00) and between Europeans and Aboriginal Australians ( p=0.00); however, they were similar for the Bangladeshi and Aboriginal Australian subjects. The allele frequency distribution of the IL-1RN (T + 2018C) SNP for the Aboriginal Australians was statistically different from the European group ( p=0.00), but it was not different from the Bangladeshi group ( p=0.09). Compared with controls of European origin, there were no significant differences in the distribution of these polymorphisms among SIDS infants or parents of SIDS infants. For the IL-1β (C-511T) SNP, the highest IL-1β responses to endotoxin were obtained with leukocytes of non-smokers with the heterozygous CT genotype. Smokers had significantly lower levels of IL-1β in response to endotoxin ( p=0.01) and these differences were significant for donors with the wild type CC ( p=0.00) and CT ( p=0.03) genotypes. Similar patterns were observed for IL-1β responses to TSST, but the differences were not significant. For the IL-1RN (T + 2018C) SNP, the highest IL-1β responses to endotoxin were obtained with leukocytes from non-smoker donors with the wildtype TT genotype and significantly lower responses were found with leukocytes from donors with the TC genotype ( p=0.02). The responses of smokers were lower but the differences were significant only for donors with the TT genotype ( p=0.00). Similar patterns were observed for IL-1β responses to TSST, but the differences were not significant. IL-1β responses to both endotoxin and TSST were increased for the small number of smokers with the TT genotype of the IL-1β (C-511T) SNP. The TT genotype of the IL-1β (C-511T) was found predominantly among Aboriginal Australian and Bangladeshi individuals but only a small proportion of Europeans. Smokers with the AA genotype of the IL-10 (G-1082A) SNP which is found predominantly among these two groups had significantly lower levels of IL-10 responses. If cigarette smoke enhances pro-inflammatory responses and reduces anti-inflammatory responses in individuals with these genotypes, this might partly explain the increased susceptibility of Aboriginal Australian infants to infections and SIDS.